The Nexus between Corporate Financial Ratio and Price Earnings Performance: Evidence from President Election Period in Indonesia - Suham Cahyono; Hendri Arya Fernando; Rieswandha Dio Primasatya (Jurnal Akuntansi dan Keuangan, 2023)
This research aims to obtain an empirical overview of the influence of financial performance on stock prices in situations of political uncertainty in Indonesia. Our sample includes all non-financial public companies listed on the Indonesia Stock Exchange from 2011 to 2019, totalling 1,899 company-years. This study uses fixed-effects regression to test the hypothesis. The researchers found that financial performance positively and negatively affects stock prices. Specifically, we found a negative relationship between financial performance proxied by Return on Equity and Debt to Ratio. In contrast, liquidity, return on Assets, and Net Profit Margin have a negative effect on financial performance. Furthermore, our evidence becomes unique when in conditions of political uncertainty, where more financial performance has a negative impact on stock prices. This study provides practical and theoretical implications to fill gaps in previous literature regarding financial performance and its influence on stock prices.